Crossing the Green Line: Frontier, environment and the role of bandeirantes in the conquering of Brazilian territory - Evans, Sterling; Dutra e Silva, Sandro (Fronteira: Journal of Social, Technological and Environmental Science, 2017)
This article’s objective is to present, via bibliographic research, the territorial makeup of colonial Brazil (1500-1822) and the Brazilian historical approach at the beginning of the twentieth century that sought to relate questions and concepts of frontier, territoriality, and nature in the historic role of the bandeirante movement. The goal here is to address territorial and geographic questions, but also environmental ones, based on historical geography, and to present arguments that fall in the nexus between history and nature in the debate on Brazilian territorial expansion. The text is grounded in classical works, and works by renown authors on this topic, but we also include discussion of less well known sources. The intent is to identify how the theme of bandeirantes and Brazilian westward expansion can be analyzed differently in the pertinent specialized historical literature.